THE EFFECT OF PLANTING MEDIA CONCENTRATION AND LIQUID ORGANIC WASTE FERTILIZER ON RICE GROWTH AND PRODUCTION LOCAL WITH POT PLANTING SYSTEM - Yuda Barkah; Sri Mahareni Br.Sitepu; M Wasito (RADJA PUBLIKA, 2024)
As a result of climate change, pest and disease attacks, unbalanced use of seeds and fertilizer use, rice production in Indonesia is still not sufficient for the domestic population. This research used a Randomized Block Design with 2 factors and 3 replications. The first factor is the Planting Media consisting of 4 levels of concentration, namely M0 = topsoil, M1 = topsoil(1) solid(1) goat manure(1), M2 = topsoil (2)solid (1) tankos (1), and M3 = topsoil (2) solid(1) cow dung(1). The second factor is POC (Liquid Organic Fertilizer) consisting of 4 levels of concentration, namely P0 = 0 cc/liter of water/plot, P1 = 200 cc/liter of water/plot, P2 = 400 cc/liter of water/plot, and P3 = 600 cc /liter of water/plot. The growth results show that the plant height parameter in the planting media factor is more dominant in the M2 treatment where from 3.4 and 5 WAP it is still the highest compared to other treatments for the Poc factor from 2,3,4 and 5 WAP it has no effect, for the number of tillers at 4, 8 and 12 WAP the highest data were for M1 and M2 for the planting media factor, while Poc at 4 WAP had no influence but at 8 and 12 WAP it had a real influence, on the number of panicles the highest results were on the planting media factor, namely M1 for Poc P3, on panicle length. for the planting media factor, namely M2 and the Poc factor P3, for the parameters wet weight and dry weight of grain there is no influence from the two factors caused by bird pests which cause loss of production